Nitrogen-sulfur co-doped silkworm excrement biochar, and preparation method and application thereof
Patent Information
- Application Number
- CN202611100052.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]目前,氮硫共掺杂、磁性复合改性多以常规农林废弃物为原料,针对蚕沙的研究较少,氮硫共掺杂耦合磁性的复合改性更是鲜有报道
[0020]本发明以蚕沙为原料,采用氮硫共掺杂与磁性负载相结合的改性策略,制备氮硫共掺杂蚕沙生物炭(NSBC),系统研究其对水中TCH的吸附性能与机理,探索最佳吸附条件和循环利用性能,以期为蚕沙资源化利用和抗生素污染治理提供一定的理论依据和技术支撑。
Smart Images

Figure CN122999137A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of silkworm excrement resource utilization and antibiotic pollution control technology, and more specifically, to a nitrogen-sulfur co-doped silkworm excrement biochar, its preparation method, and its application. Background Technology
[0002] In recent years, emerging pollutants have gradually become a focus of environmental attention. These substances generally possess characteristics such as biotoxicity, environmental persistence, and bioaccumulation, thus posing a significant threat to ecosystems and human health. Tetracycline hydrochloride (TCH), as a broad-spectrum antibiotic, is widely used in the medical, pharmaceutical, and livestock industries due to its low production cost and broad antibacterial range. However, TCH is difficult to completely metabolize in organisms, and large quantities enter water bodies in its original form or as metabolites. Antibiotic residues not only lead to the emergence of drug-resistant strains and disrupt the balance of aquatic ecosystems, but may also harm human health through the food chain.
[0003] Currently, the removal of antibiotics from water bodies mainly includes advanced oxidation, membrane separation, biodegradation, and... In contrast, adsorption methods are widely used in practical engineering due to their low cost, environmental friendliness, and low energy consumption. The core of adsorption technology lies in the selection and performance optimization of adsorption materials. Carbon-based materials (activated carbon, biochar, carbon nanotubes, etc.) are widely used for the adsorption and removal of antibiotic pollutants in water bodies due to their advantages such as large specific surface area and well-developed pore structure.
[0004] Biochar is a carbon-rich material produced by the pyrolysis of biomass such as agricultural and forestry waste and agricultural byproducts under oxygen-limited or anaerobic conditions. It boasts abundant raw materials, low cost, and multiple environmental benefits, leading to increasing research and application in the environmental field in recent years. Silkworm excrement is a major solid waste product of the sericulture industry. Currently, a large amount of silkworm excrement produced annually in my country is still disposed of through stockpiling or incineration, resulting in resource waste and ecological burden. The high proportion of cellulose, lignin, and protein in silkworm excrement makes it a significant potential source of biochar.
[0005] However, raw biochar generally suffers from a lack of surface functional groups and poor controllability of specific surface area and pore structure, requiring further modification to improve adsorption performance. Common modification strategies include heteroatom doping, magnetic material composites, acid-base activation, and redox treatment. Among these, heteroatom doping introduces heterogeneous elements such as nitrogen, sulfur, phosphorus, and boron into the carbon skeleton of biochar, thereby regulating the electronic structure, surface chemical properties, and defective active sites of the material, significantly enhancing its adsorption capacity for pollutants. The synergistic effect of different heteroatoms in the carbon skeleton may lead to even better modification results. In recent years, nitrogen-sulfur co-doped biochar has attracted widespread attention. N and S co-doping can simultaneously improve the adsorption performance of biochar, making it exhibit superior performance in water treatment processes.
[0006] Currently, nitrogen-sulfur co-doping and magnetic composite modification mostly use conventional agricultural and forestry waste as raw materials, with limited research on silkworm excrement, and even fewer reports on nitrogen-sulfur co-doping coupled with magnetic composite modification. Summary of the Invention
[0007] The purpose of this invention is to provide a nitrogen-sulfur co-doped silkworm excrement biochar, its preparation method, and its application. Using silkworm excrement as raw material, a modification strategy combining nitrogen-sulfur co-doping and magnetic loading is adopted to prepare nitrogen-sulfur co-doped silkworm excrement biochar (NSBC). The adsorption performance and mechanism of NSBC on TCH in water are systematically studied, and the optimal adsorption conditions and recycling performance are explored, in order to provide a certain theoretical basis and technical support for the resource utilization of silkworm excrement and the treatment of antibiotic pollution.
[0008] The above-mentioned technical objective of the present invention is achieved through the following technical solution: a method for preparing nitrogen-sulfur co-doped silkworm excrement biochar, comprising the following steps:
[0009] S1. Grind the silkworm excrement into powder and pass it through a 60-mesh sieve. Weigh the raw materials according to the following ratio: silkworm excrement: anhydrous sodium carbonate: thiourea: ferric chloride = 1:1:1.5:0.6. Put all the raw materials into a mortar and grind them. Transfer the resulting mixture to a porcelain crucible, add pure water and stir until a moist paste is formed. Let it stand at room temperature for 2 hours to age.
[0010] S2. The aged paste was dried in an oven at 80°C for 7 hours. Then, the porcelain crucible was covered and transferred to a muffle furnace and calcined at 550°C for 2 hours.
[0011] S3. After cooling, remove the product and wash it twice with deionized water and anhydrous ethanol alternately. Detect its pH and adjust the pH according to the test results. Wash it with deionized water until neutral and finally dry it to constant weight to obtain nitrogen-sulfur co-doped silkworm excrement biochar.
[0012] The present invention is further configured such that the raw materials in S1 are weighed as follows: 10g of sieved silkworm excrement powder, 10g of anhydrous sodium carbonate, 15g of thiourea, and 6g of ferric chloride are weighed.
[0013] The present invention is further configured such that: when the pH is detected to be strongly alkaline in step S3, the pH is adjusted by acid soaking.
[0014] The present invention further provides nitrogen-sulfur co-doped silkworm excrement biochar prepared by the above method.
[0015] This invention further provides the application of nitrogen-sulfur co-doped silkworm excrement biochar in the adsorption of TCH in water.
[0016] The present invention further specifies that the optimal process conditions for the adsorption of TCH by the nitrogen-sulfur co-doped silkworm excrement biochar are: pH value of 8 and initial concentration of 15 mg·L⁻¹. -1 The dosage was 0.07 g, and the adsorption time was 300 min.
[0017] The present invention is further configured such that the nitrogen-sulfur co-doped silkworm excrement biochar is recyclable.
[0018] The present invention is further configured such that: the method for recycling the nitrogen-sulfur co-doped silkworm excrement biochar is as follows: the adsorbed material is first treated with deionized water at 25°C and 165 r·min -1 The adsorption solution is desorbed by shaking in a constant temperature shaker for 60 min, centrifuged for 5 min, and repeated twice. Then, it is desorbed by anhydrous ethanol under the same conditions for 120 min, centrifuged for 5 min, and then washed multiple times with deionized water until the filtrate is neutral. Finally, it is dried in an oven at 60℃ and ready for the next adsorption.
[0019] In summary, the present invention has the following beneficial effects:
[0020] This invention uses silkworm excrement as raw material and employs a modification strategy combining nitrogen-sulfur co-doping and magnetic loading to prepare nitrogen-sulfur co-doped silkworm excrement biochar (NSBC). The adsorption performance and mechanism of NSBC on TCH in water are systematically studied, and the optimal adsorption conditions and recycling performance are explored, in order to provide a certain theoretical basis and technical support for the resource utilization of silkworm excrement and the treatment of antibiotic pollution.
[0021] The prepared NSBC surface exhibits a porous structure with sheet-like stacking, and nitrogen, sulfur, and iron elements are uniformly doped into the carbon framework; the adsorption mechanism of TCH by NSBC mainly involves electrostatic attraction, hydrogen bonding, complexation, and pore diffusion.
[0022] NSBC exhibits a wide pH adaptability range, and its adsorption performance is improved by 2 times after modification. The optimal process conditions for its adsorption of TCH are: pH 8 and initial concentration of 15 mg·L⁻¹. -1The dosage was 0.07 g, and the adsorption time was 300 min. At this time, the adsorption rate reached 94.68%.
[0023] The adsorption process is more consistent with pseudo-second-order kinetics and the Langmuir model, and the reaction can proceed spontaneously and is an endothermic reaction.
[0024] In HCO3 - Cl - SO4 2- In wastewater containing coexisting anions, NSBC exhibits good selectivity for adsorbing TCH.
[0025] After four cycles, NSBC maintained an adsorption rate of 76.38% for TCH, demonstrating excellent adsorption and regeneration performance.
[0026] This invention provides a new approach for the resource utilization of silkworm excrement and the control of antibiotic pollution, and is of great significance for promoting the resource utilization of silkworm excrement and ecological environmental protection. Attached Figure Description
[0027] Figure 1 This is a flowchart of the NSBC preparation process in this invention;
[0028] Figure 2 This is the standard curve of tetracycline hydrochloride in this invention;
[0029] Figure 3 This invention relates to the effect of dosage on the adsorption of TCH by NSBC.
[0030] Figure 4 This invention relates to the effect of pH on the adsorption of TCH by NSBC.
[0031] Figure 5 This invention relates to the effect of time on the adsorption of TCH by NSBC.
[0032] Figure 6 This invention relates to the effect of NSBC concentration on TCH adsorption.
[0033] Figure 7 This invention relates to the effect of temperature on the adsorption of TCH by NSBC.
[0034] Figure 8 This is a schematic diagram of the results of the anion interference experiment in this invention;
[0035] Figure 9 This is a comparison chart of the adsorption amount and adsorption rate of the material before and after modification in this invention.
[0036] Figure 10 This is a schematic diagram showing the results of the adsorption regeneration experiment in this invention;
[0037] Figure 11 These are the pseudo-first-order dynamic fitting curve (left) and pseudo-second-order dynamic fitting curve (right) in this invention;
[0038] Figure 12 These are the Langmuir isotherm fitting curve (left) and the Freunndlich isotherm fitting curve (right) in this invention;
[0039] Figure 13 These are the FT-IR spectra of the raw material (BC) and NSBC before and after adsorption in this invention;
[0040] Figure 14 These are XRD patterns of the original powder (BC) and NSBC before and after adsorption in this invention;
[0041] Figure 15 This is the XPS image (top) of NSBC before and after adsorption in this invention;
[0042] Figure 16 The following is an XPS image of NSBC before and after adsorption in this invention (below);
[0043] Figure 17 These are SEM images of BC and NSBC before and after adsorption, as well as EDS surface and spot scans showing the content and distribution of S, Fe, C, N, and O.
[0044] Figure 18 This is the zero-point potential characterization diagram of NSBC in this invention;
[0045] Figure 19 This is the VSM diagram of NSBC in this invention;
[0046] Figure 20 This is a diagram illustrating the reaction mechanism of NSBC adsorption of TCH in this invention. Detailed Implementation
[0047] The following is in conjunction with the appendix Figure 1-20 The present invention will be described in further detail below.
[0048] The main reagents and instruments used in the examples are as follows:
[0049] Table 1 Main reagents used in the experiment
[0050]
[0051] Table 2 Main Experimental Instruments
[0052]
[0053] Example 1: Preparation of nitrogen-sulfur co-doped silkworm excrement biochar
[0054] After grinding and pulverizing silkworm excrement through a 60-mesh sieve, the raw materials (BC) were weighed according to the following ratio: silkworm excrement: anhydrous sodium carbonate: thiourea: ferric chloride = 1:1:1.5:0.6. 10 g of the sieved silkworm excrement powder, 10 g of anhydrous sodium carbonate, 15 g of thiourea, and 6 g of ferric chloride were weighed and ground in a mortar. The resulting mixture was transferred to a porcelain crucible, and purified water was added and stirred until a moist paste was formed. The mixture was allowed to stand at room temperature for 2 hours. The aged paste was then dried in an oven at 80°C for 7 hours. The porcelain crucible was then covered and transferred to a muffle furnace and calcined at 550°C for 2 hours. After cooling, the mixture was removed and washed twice alternately with deionized water and anhydrous ethanol, recording the initial pH. Depending on the pH, if the alkalinity was strong, acid soaking could be used appropriately. The mixture was then washed with deionized water only until neutral, and finally dried to constant weight to obtain nitrogen-sulfur co-doped silkworm excrement biochar.
[0055] The nitrogen-sulfur co-doped silkworm excrement biochar prepared in Example 1 and the material before modification were characterized:
[0056] The infrared absorption spectra of biochar were measured using Fourier transform infrared spectroscopy (FTIR) to investigate the changes in functional groups before and after material modification and adsorption. The FT-IR characterization results of the raw material and NSBC before and after adsorption are as follows: Figure 13 As shown in the figure, the infrared spectral peak shapes of the raw material and NSBC before and after adsorption did not change significantly. Specifically, the peak shapes in the 3500~3250 cm⁻¹ range are... -1 The absorption peaks within this range correspond to the stretching vibrations of -OH or -NH; 1621.51 cm⁻¹ -1 and 1623.07 cm -1 The peak corresponds to the C=C stretching vibration; 1432.52 cm -1 The peak at that location corresponds to the stretching vibration of CH. After modification, the disappearance of the CH stretching vibration peak of the raw material may be because the aliphatic components in the material are decomposed after pyrolysis, and the carbon skeleton is transformed into an aromatic structure. After modification and adsorption, the stretching vibration peaks of -OH and C=C are shifted, and the peak intensities also change, indicating that these functional groups participate in the adsorption of TCH.
[0057] X-ray diffraction (XRD) was used to analyze the crystal structure and phase composition of the original powder and the material before and after adsorption. The XRD patterns of the original powder and NSBC before and after adsorption are shown below. Figure 14As shown, the characteristic peak at 29.31° of the original powder indicates the formation of a carbon-rich solid material, i.e., amorphous biochar material. The diffraction peaks of NSBC at 36.85°, 56.20°, and 61.65° largely correspond to the characteristic peaks in the Fe3O4 standard spectrum (PDF#97-018-3977), indicating that NSBC is loaded with a certain degree of magnetism. From the diffraction results, the diffraction peak signals attributed to Fe3O4 are relatively weak, and some crystal plane characteristic peaks are not even clearly visible, reflecting the poor magnetism of the material.
[0058] The magnetic properties of the material were characterized using a vibrating sample magnetometer (VSM). Figure 19 As can be seen, although the saturation magnetization of NSBC is only 0.0831 emu·g -1 Furthermore, its magnetization curve is "S"-shaped, indicating that its magnetism is relatively weak. However, the material still has the ability to separate from the water phase under the action of a magnetic field, thus laying a feasible foundation for its recycling and regeneration.
[0059] The morphology of the materials before and after adsorption, as well as the pure silkworm excrement powder before modification, was characterized using scanning electron microscopy (SEM). Figure 17 It can be seen that at the same magnification of 20,000x and 50,000x, the BC surface has many pores and exhibits obvious granular structure, reflecting that silkworm excrement itself has certain adsorption properties. After N and S doping, the NSBC surface is smoother and exhibits a plate-like structure with obvious pores, which helps to improve adsorption performance. The surface of the adsorbed NSBC is even smoother, with larger blocky deposits and reduced pore structure. EDS analysis shows that S, Fe, C, N, and O are the main constituent elements of NSBC, and N and S are relatively uniformly distributed on its surface, reflecting that the preparation of NSBC has achieved a relatively ideal effect.
[0060] The surface elemental composition and chemical state of the material before and after adsorption were analyzed using X-ray photoelectron spectroscopy (XPS). Figure 15 The full spectrum of NSBC before and after adsorption (a) shows that N and S elements were successfully incorporated into the biochar, indicating successful material modification. The Fe2p content was 1.98%, indicating successful magnetization. After adsorption, the C1s content of NSBC decreased to 42.98%, while the Fe2p content increased to 4.11%. This may be because some amorphous carbon was removed from the NSBC surface during adsorption, resulting in more Fe3O4 particles being exposed on the material surface. The increased proportion of O and N atoms further indicates that TCH was effectively loaded into the material. Figure 15 (b) shows the C1s curves before and after NSBC adsorption. At 284.80 eV, 286.34 eV, and 288.64 eV, respectively, CC or C=C, CO or CN, and C=O or OC=O are represented. Figure 15From (c), it can be seen that in the O1s spectrum of NSBC, 530.68 eV, 531.80 eV, and 533.18 eV correspond to Fe-O, C=O, CO, or H2O, respectively; from Figure 16 (a) N1s spectra before and after NSBC adsorption and Figure 16 From the S2p spectra before and after NSBC adsorption in (b), it can be seen that 398.47 eV, 399.87 eV, 401.97 eV and 163.77 eV, 164.87 eV, 169.00 eV correspond to the S2p of pyridine N, pyrrole N or amino N, graphite N and thiophene sulfide CSC, respectively. 3 / 2 and S2p 1 / 2 -SO x Pyrrole N and thiophene sulfide are recognized as active redox reaction centers. Figure 16 (c) shows the Fe2p spectra before and after NSBC adsorption. 712.19 eV, 716.76 eV, and 725.70 eV correspond to Fe2p values respectively. 3 / 2 Satellite peaks and Fe2p 1 / 2 .
[0061] The surface charge properties of the material were determined by zero-point potential characterization. The effect of pH on adsorption was mainly due to the surface charge of NSBC and the pH-dependent speciation of TCH. Figure 18 It can be seen that the zero-point potential (pH) of NSBC PZC The pH value is 2.36. When the solution pH < 2.36, the material surface becomes positively charged due to protonation. At this time, TCH mainly exists in the form of cations, and the material and TCH will have electrostatic repulsion, which is not conducive to adsorption. When the solution pH > 2.36, the material will deprotonate and become negatively charged. As the solution pH gradually increases, the form of TCH also changes from cation to zwitterion and finally to anion. During this process, the electrostatic attraction gradually weakens and then the electrostatic repulsion gradually strengthens. However, under the combined effect of electrostatic interaction, hydrogen bonding, and π-π stacking, NSBC can maintain good adsorption performance over a wide pH range.
[0062] Example 2: Application of nitrogen-sulfur co-doped silkworm excrement biochar
[0063] 1. Plotting the TCH standard curve
[0064] Concentrations of 0, 1, 2, 4, 6, 8, and 10 mg·L⁻¹ were prepared using a serial dilution method. -1 The absorbance of TCH standard solutions at various concentrations was determined using UV-Vis spectrophotometry. A standard curve was plotted with TCH concentration on the x-axis and corresponding absorbance on the y-axis. The standard curve is shown below. Figure 2 As shown.
[0065] 2. Experiment on the effect of TCH adsorption performance
[0066] This study investigated the effects of biochar dosage, pH, reaction time, initial TCH concentration, and temperature on the adsorption performance of biochar on TCH. The adsorption capacity Q and adsorption rate E were calculated to provide a basis for determining optimal conditions and evaluating the adsorption effect of biochar. The calculation formulas are as follows:
[0067]
[0068]
[0069] In the formula:
[0070] C0, C e The concentrations of the TCH solution before and after adsorption are in mg·L⁻¹. -1 ;
[0071] V is the volume of wastewater, in mL;
[0072] m represents the dosage of NSBC, expressed in grams.
[0073] The specific methods for studying adsorption performance are as follows:
[0074] (1) Effect of biochar dosage: Weigh 0.01, 0.03, 0.04, 0.05, 0.07, 0.09, and 0.11 g of NSBC respectively, pH=5, and measure 50 mL of NSBC with a concentration of 10 mg·L⁻¹. -1 The TCH solution was added to an Erlenmeyer flask and placed on a shaker (165 r·min). -1 The reaction was carried out at 25℃ for 180 min. Then, the reaction solution was filtered through a 0.45 μm filter membrane, and an appropriate amount of filtrate was taken. The mass concentration of the remaining TCH was determined by UV-Vis spectrophotometry, and the removal rate E and adsorption capacity Q of TCH were calculated and recorded.
[0075] like Figure 3 As shown, the adsorption rate of TCH by the material first increases and then decreases with increasing dosage, and the adsorption capacity gradually decreases. When the dosage is 0.05, 0.07, and 0.09 g, the adsorption rates reach 94.09%, 95.58%, and 94.39%, respectively. Afterward, with further increases in dosage, the rate of increase in removal rate slows down and slightly decreases. This may be because the addition of excessive NSBC leads to competition between adsorption sites, preventing TCH molecules from fully occupying adsorption sites, thus reducing the removal rate. At a dosage of 0.07 g, the removal rate reaches 95.58%, and the adsorption capacity is 6.827 mg·g⁻¹. -1Excessive dosage not only increases costs but also makes subsequent separation and recovery more difficult. Therefore, considering both adsorption efficiency and economic benefits for practical applications, a dosage of 0.07 g of biochar was selected for subsequent experiments.
[0076] (2) Effect of pH value: With other conditions fixed, the biochar dosage was set to 0.07 g, and the pH was adjusted to a series of gradients of 3, 4, 5, 6, 7, 8, and 9.
[0077] from Figure 4 As can be seen, the adsorption rate of TCH is highest at pH 8, therefore the pH for subsequent experiments was set at 8. Within the initial pH range of 3 to 9, the removal rate of TCH by NSBC remained at a relatively high level of 83.71% to 89.94%, indicating that NSBC has a wide pH adaptability range. This characteristic improves its applicability in practical applications, because the effluent from conventional biological wastewater treatment is often weakly alkaline, requiring pH adjustment. The pH adaptability of NSBC can effectively simplify the process and reduce treatment costs.
[0078] The complex variation in adsorption rate with pH is the result of the combined effects of TCH molecular morphology transformation and NSBC surface charge state. TCH is an amphoteric compound; when pH ≤ 3.3, TCH mainly exists in the cationic form (TCH). 3+ TCH exists as a zwitterion (TCH) at pH values between 3.3 and 7.7. 0 It exists, and in pH between 7.7 and 9.7 and pH > 9.7, it is present as TCH. - and TCH 2- exist ] In the pH range of 3–5, TCH exists primarily in cationic form, while the NSBC surface carries a negative charge, which is conducive to adsorption; therefore, the adsorption rate increases with increasing pH. In the pH range of 5–7, TCH gradually transforms from a cationic to a zwitterionic form, becoming electrically neutral overall. This weakens the electrostatic interaction with the material surface, and non-electrostatic interactions such as hydrogen bonding and π-π stacking become the main driving forces for adsorption. However, their binding strength may be relatively weak, leading to a slight decrease in the adsorption rate. When pH = 7–8, TCH begins to transform from a zwitterionic to anionic, while the negative charge on the NSBC surface increases. At this point, the adsorption rate increases instead of decreasing. This may be because, simultaneously with the onset of electrostatic repulsion, the polar groups exposed during the TCH molecular transformation form stronger hydrogen bonds with the functional groups on the NSBC surface. At the same time, a strong π-π stacking interaction occurs between the aromatic rings in the TCH molecule and the graphitized structure of NSBC. The enhancement of these non-electrostatic adsorption mechanisms outweighs the negative effects of electrostatic repulsion. As the pH increases from 8 to 9, NSBC carries more negative charge, TCH exists in anionic form, and the electrostatic repulsion gradually increases, thus the adsorption rate decreases slightly.
[0079] (3) Effect of reaction time: The reaction times were set to 30, 60, 90, 120, 180, 240, 300 and 360 min respectively, while the other conditions remained unchanged.
[0080] Figure 5 The results showed that the adsorption rate and adsorption capacity of NSBC for TCH increased continuously with increasing reaction time, and tended to stabilize after 300 min, at which point the adsorption rate was 90.83% and the adsorption capacity was 6.488 mg·g⁻¹. -1 In the initial stage of adsorption, the concentration of TCH in the solution is high, and there are sufficient active sites on the NSBC surface. The combined effect of these two factors leads to a rapid increase in both the adsorption rate and the adsorption capacity. As adsorption progresses, the concentration of TCH in the solution gradually decreases, and the active adsorption sites on the NSBC surface also tend to become saturated. At this point, the rate of increase in both the adsorption rate and the adsorption capacity gradually decreases. When the adsorption sites on the NSBC surface are completely saturated, adsorption reaches equilibrium. Experimental results show that the adsorption rate and adsorption capacity remain essentially unchanged after 300 min of reaction, indicating that adsorption equilibrium has been reached. Therefore, the reaction time was set to 300 min in subsequent experiments.
[0081] (4) Effect of initial TCH concentration: With other conditions unchanged, the reaction time was 300 min, and the concentration gradients were 5, 10, 15, 20, 40, 60, 80, and 100 mg·L⁻¹. -1 TCH solution.
[0082] like Figure 6 As shown, with increasing TCH concentration, the adsorption of TCH by NSBC initially increases and then decreases, while the adsorption capacity maintains an upward trend before eventually stabilizing. At lower initial concentrations, the NSBC surface provides relatively abundant adsorption sites, resulting in a rapid increase in adsorption rate. However, the number of adsorption sites on the NSBC surface is limited. As the TCH concentration gradually increases, NSBC gradually reaches adsorption saturation; therefore, the adsorption rate of TCH by NSBC decreases with increasing concentration. When the TCH solution concentration is 15 mg·L⁻¹... -1 At that time, the adsorption rate was 97.65%, therefore, subsequent experiments determined the standard value of the simulated TCH concentration to be 15 mg·L⁻¹. -1 .
[0083] (5) Effect of temperature: Select four temperature points of 25, 35, 45 and 55℃ as variables, and keep the other conditions unchanged.
[0084] Depend on Figure 7It can be seen that when the temperature rises from 25℃ to 55℃, the adsorption rate and adsorption amount of TCH by NSBC show an increasing trend. This is because as the temperature increases, the thermal motion of molecules intensifies, the diffusion rate of TCH molecules accelerates, and the probability of collision with the NSBC surface increases, thereby increasing the probability of binding to the active sites. This further confirms that the adsorption process is an endothermic reaction, and that increasing temperature is beneficial to adsorption.
[0085] (6) Based on the results of single-factor experiments, determine the conditions of orthogonal experiments, systematically evaluate the effects of individual and synergistic effects of each factor on the adsorption of TCH by NSBC, use range analysis to determine the optimal process conditions, and verify their stability.
[0086] The orthogonal experiment investigated four factors: pH value, initial concentration of simulated wastewater, dosage, and adsorption time, with three levels for each. The experimental design and results are detailed in Table 3.
[0087] Table 3 shows that the optimal process conditions are: pH 8 and initial concentration 15 mg·L⁻¹. -1 The dosage was 0.07 g, and the adsorption time was 300 min. Under these conditions, the adsorption rate of NSBC for TCH reached 94.68%. Further analysis of the influence of various factors on the adsorption performance was conducted using the range R-value. The results showed that the initial concentration of the simulated wastewater resulted in the largest R-value, indicating that this factor had the greatest impact on the TCH adsorption performance of NSBC.
[0088] Table 3 Orthogonal Experiments and Results
[0089]
[0090] (7) By comparing the adsorption rate and adsorption amount of TCH on the material before and after modification, it can be determined whether the adsorption performance has been improved after modification treatment, thus providing data support for the optimization of modification methods.
[0091] To evaluate the adsorption stability of the material for TCH, three parallel control experiments were conducted under optimal conditions, and the average adsorption rate and relative standard deviation were calculated. The experimental results are shown in Table 4.
[0092] As shown in Table 4, the highest TCH adsorption rate measured in the three experiments was 94.68%, and the lowest was 91.51%, with an absolute difference of only 0.0317, indicating minimal fluctuation. The average adsorption rate and relative standard deviation were 92.96% and 1.72%, respectively. The relative standard deviation was less than 5%, demonstrating that the material's adsorption performance was stable and good.
[0093] Table 4 Material stability results
[0094]
[0095] like Figure 9 As shown, under optimal process conditions, the adsorption rate of the unmodified material in the TCH adsorption control experiment was 43.22%, and the adsorption capacity was 6.48 mg·g. -1 Therefore, it can be seen that the modified composite material exhibits better adsorption performance compared with the original powder.
[0096] 3. Anion coexistence interference experiment
[0097] To investigate the effect of the presence of coexisting anions on the adsorption performance of biochar, HCO3- was selected. - Cl - SO4 2- HPO4 2- Four anions were used as representative interference factors. The specific experimental steps are as follows: 1 mol·L⁻¹ anions were prepared respectively. -1 NaHCO3, NaCl, Na2SO4 solution and 0.2 mol·L -1 Using Na2HPO4·12H2O solution as the mother liquor, a TCH mother liquor concentration of 300 mg·L was prepared. -1 Take a certain volume of the mother liquor separately, and adjust the volume of the mixed solution to 50 mL. The final concentration is 0.01 mol·L⁻¹. -1 The pH of the solution after volume adjustment was adjusted to 8; under the optimal process parameters, further adsorption experiments were carried out on each system and the data were recorded.
[0098] like Figure 8 As shown, the presence of all four anions interferes with the TCH adsorption process to varying degrees. The TCH removal rate before the introduction of coexisting anions was 93.10%. The introduction of HCO3... - Cl - SO4 2- The adsorption rates of the material for TCH were 91.71%, 90.92%, and 90.13% respectively, showing a slight impact; while the introduction of HPO4... 2- The adsorption rate of the material for TCH decreased to 79.45%, indicating a significant impact. The adsorption rate also decreased to 77.86% when four anions were mixed, but this was not observed when HPO4 was excluded. 2- After the ion was removed, the adsorption rate of the other three anions was 91.91% when mixed, indicating that the effect was not significant. This suggests that the decrease in adsorption rate was mainly attributed to HPO4. 2- Introduction of ions. HPO4 2- The inhibitory effect on adsorption may be due to HPO4. 2- After hydrolysis, it competed with TCH molecules for adsorption at the active sites on the NSBC surface, possibly due to its higher charge, which allowed it to occupy a large portion of the NSBC surface. This increases the electrostatic repulsion between NSBC and TCH, thereby reducing the adsorption rate of TCH by NSBC. In contrast, HCO3... - Cl - SO4 2- The interaction between ions and the NSBC surface is relatively weak, resulting in less competition for adsorption sites.
[0099] In summary, although HPO4 2- While there is a significant inhibitory effect, NSBC still exhibits relatively good adsorption selectivity for TCH under the coexistence conditions of most common anions.
[0100] 4. Regeneration Experiment
[0101] The fixed solid-liquid ratio is 1:30 g·mL -1 The adsorbed material was first treated with deionized water at 25°C and 165 r·min. -1 The material was desorbed by shaking in a constant-temperature shaker for 60 min, centrifuged for 5 min, and repeated twice. Then, it was desorbed with anhydrous ethanol under the same conditions for 120 min, centrifuged for 5 min, and washed repeatedly with deionized water until the filtrate was neutral. Finally, it was dried in a 60℃ oven. 0.05 g of the desorbed material was weighed and adsorption experiments were conducted under optimal process parameters. After the reaction was completed, the residual TCH mass concentration was measured, and the adsorption rate was calculated. The above steps were repeated for four adsorption regeneration experiments to evaluate the reusability of the material. Figure 10 It can be seen that after 4 cycles of use, NSBC still retains an adsorption rate of 76.38% for TCH, corresponding to an adsorption capacity of 11.46 mg·g⁻¹. -1 It exhibits good renewable properties, enabling the reuse of materials.
[0102] 5. Adsorption kinetics fitting
[0103] By fitting pseudo-first-order and pseudo-second-order kinetic models to the experimental data, the mechanism of NSBC adsorption of TCH and the influence of various factors on the adsorption kinetic process were elucidated. The pseudo-first-order and pseudo-second-order kinetic calculation models are as follows:
[0104]
[0105]
[0106] In the formula:
[0107] q t The adsorption amount of TCH at time t is mg·g. -1 ;
[0108] q e The adsorption capacity of TCH under equilibrium conditions is expressed in mg·g⁻¹.-1 ;
[0109] k1 and k2 are both reaction kinetic rate constants, in g·(mg·min). -1
[0110] Figure 11 The results in Table 5 show that the linear correlation coefficients for the pseudo-first-order and pseudo-second-order kinetic fits are 0.96156 (R1) and 0.99928 (R2), respectively. The latter is significantly closer to 1 and higher than the former. Therefore, the adsorption process of NSBC on TCH is more consistent with the pseudo-second-order kinetic model and belongs to chemisorption.
[0111] Table 5. Dynamic Relevant Parameters
[0112]
[0113] 6. Adsorption thermodynamic model
[0114] (1) Adsorption isotherm model
[0115] Adsorption isotherms reveal the equilibrium distribution of adsorbate in the solid-liquid two-phase system under isothermal conditions, a relationship fundamental to exploring adsorption behavior and mechanisms. Experimental data on the adsorption of TCH by NSBC were fitted using the Langmuir and Freundlich models to elucidate its adsorption characteristics. The Langmuir model is commonly used to describe physisorption or monolayer chemisorption processes, while the Freundlich model is frequently used to describe heterogeneous or multilayer adsorption.
[0116]
[0117]
[0118] In the formula:
[0119] q m This represents the amount of TCH adsorbed at adsorption equilibrium, expressed in mg·g⁻¹. -1 ;
[0120] C e This represents the mass concentration of TCH in the solution at adsorption equilibrium, in mg·L⁻¹. -1 ;
[0121] 'a' represents a constant related to the adsorption energy;
[0122] k1 and k2 represent the adsorption equilibrium constants of Langmuir and Freundlich, respectively;
[0123] 1 / n represents the adsorption index. It is generally believed that adsorption is easy when 0.1≤1 / n≤0.5 and difficult when 1 / n>2.
[0124] from Figure 12 As shown in Table 6, the adsorption process of TCH by NSBC is more in line with the Langmuir model (R1>R2), and the adsorption index 1 / n is 0.320 (0<1 / n<1), indicating good adsorption performance.
[0125] Table 6. Fitting parameters for adsorption isotherms
[0126]
[0127] (2) Thermodynamic parameters
[0128] Based on the adsorption isotherm data, the Gibbs free energy, enthalpy change ΔH, and entropy change ΔS are calculated using the following formulas:
[0129]
[0130]
[0131]
[0132] In the formula:
[0133] k represents the standard adsorption equilibrium constant;
[0134] T is the thermodynamic temperature;
[0135] R is the gas constant 8.314 (J·mol⁻¹). -1 ·K -1 ).
[0136] Based on the above calculations, the relevant thermodynamic parameters can be obtained in Table 7. Table 7 shows that ΔG < 0, indicating that the reaction is spontaneous; the entropy change ΔS > 0, indicating that adsorption is an entropy-increasing process; and the enthalpy change ΔH > 0, confirming that the reaction is endothermic.
[0137] Table 7 Adsorption thermodynamic parameters
[0138]
[0139] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A method for preparing nitrogen-sulfur co-doped silkworm excrement biochar, characterized in that: Includes the following steps: S1. Grind the silkworm excrement into powder and pass it through a 60-mesh sieve. Weigh the raw materials according to the following ratio: silkworm excrement: anhydrous sodium carbonate: thiourea: ferric chloride = 1:1:1.5:0.
6. Put all the raw materials into a mortar and grind them. Transfer the resulting mixture to a porcelain crucible, add pure water and stir until a moist paste is formed. Let it stand at room temperature for 2 hours to age. S2. The aged paste was dried in an oven at 80°C for 7 hours. Then, the porcelain crucible was covered and transferred to a muffle furnace and calcined at 550°C for 2 hours. S3. After cooling, remove the product and wash it twice with deionized water and anhydrous ethanol alternately. Detect its pH and adjust the pH according to the test results. Wash it with deionized water until neutral and finally dry it to constant weight to obtain nitrogen-sulfur co-doped silkworm excrement biochar.
2. The method for preparing nitrogen-sulfur co-doped silkworm excrement biochar according to claim 1, characterized in that: The raw materials in S1 are weighed as follows: 10 g of sieved silkworm excrement powder, 10 g of anhydrous sodium carbonate, 15 g of thiourea, and 6 g of ferric chloride.
3. The method for preparing nitrogen-sulfur co-doped silkworm excrement biochar according to claim 1, characterized in that: When the pH is detected to be strongly alkaline in step S3, the pH is adjusted by soaking in a weak acid.
4. Nitrogen-sulfur co-doped silkworm excrement biochar prepared by the method according to any one of claims 1-3.
5. The application of nitrogen-sulfur co-doped silkworm excrement biochar according to claim 4 in the adsorption of TCH in water.
6. The application of nitrogen-sulfur co-doped silkworm excrement biochar according to claim 5 in the adsorption of TCH in water, characterized in that: The optimal process conditions for the adsorption of TCH by nitrogen-sulfur co-doped silkworm excrement biochar are: pH 8 and initial concentration of 15 mg·L⁻¹. -1 The dosage was 0.07 g, and the adsorption time was 300 min.
7. The application of nitrogen-sulfur co-doped silkworm excrement biochar according to claim 1 in the adsorption of TCH in water, characterized in that: The nitrogen-sulfur co-doped silkworm excrement biochar can be recycled.
8. The application of nitrogen-sulfur co-doped silkworm excrement biochar according to claim 1 in the adsorption of TCH in water, characterized in that: The method for recycling nitrogen-sulfur co-doped silkworm excrement biochar is as follows: the adsorbed material is first rinsed with deionized water at 25℃ and 165 r·min. -1 The adsorption solution is desorbed by shaking in a constant temperature shaker for 60 min, centrifuged for 5 min, and repeated twice. Then, it is desorbed by anhydrous ethanol under the same conditions for 120 min, centrifuged for 5 min, and then washed multiple times with deionized water until the filtrate is neutral. Finally, it is dried in an oven at 60℃ and ready for the next adsorption.
